Pengaruh Profitabilitas Dan Kebijakan Dividen Terhadap Nilai Perusahaan Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Muhamad Dendy Istigfarullah; Feny Fidyah (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to determine and analyze the influence of Profitability, measured by Return on Assets (ROA) and Return on Equity (ROE), and Dividend Policy, measured by the Dividend Payout Ratio (DPR), on Firm Value in Food and Beverage Sub-Sector Companies listed on the Indonesia Stock Exchange for the period 2019-2023. The sampling method uses a purposive sampling technique. The sample in this study is Food and Beverage Sub-Sector Companies listed on the Indonesia Stock Exchange. Thus, a sample of 7 Food and Beverage Sub-Sector Companies was obtained. The data used are secondary data obtained from annual financial reports on the official website of the Indonesia Stock Exchange, namely www.idx.co.id, and the official websites of each company. This research method uses a quantitative method with data analysis tools using multiple linear regression models with the IBM SPSS processing tool. The results of this study indicate that the ROE variable affects Firm Value. Meanwhile,  the ROA and DPR variables do not affect stock prices. Simultaneously (together) ROA, ROE, and DPR affect Firm Value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period.